Social diagnostics of information security of digital society: methodological and regulatory aspects - M. V. Kibakin (Цифровая социология)
A holistic expert method of social diagnostics of information security of the Russian society, which in its methodological and regulatory framework is based on the concept of national security, as the ability of state and public institutions to resist threats to the interests of the individual, society and the state has been presented. The essence of digital society as an object of protection from adverse effects at the technological level (computer, software and hardware base of digital communications), as well as at the level of content distributed in the information and communication network “Internet” has been stated. The subjects of virtual communication in terms of their capabilities and practice of protection from adverse information impact have been described. The characteristic of various situations of social interaction, which may be threatened by unauthorized access to personal information – in financial, economic and official relations, – has been given.A separate analysis has been made of the status of officials-subjects of the implementation of state powers in the authorities, which may be particularly vulnerable in the weak regulation © The Author(s), 2019. This is an open access article under the CC BY 4.0 license (http://creativecommons.org/licenses/by/4.0/). of malicious dissemination of false information in the information and communication network “Internet”. Special attention has been paid to the substantiation of the possibilities of early detection of information threats to the functioning of basic social institutions – social trust and stability of social relations, solidarity, civilizational identity, interfaith peace and tolerance in a complex society.The author’s methodology has been presented in the article as a sociological research technology that includes the interpretation and operationalization of groups of information threats enshrined in the state concept of national security, the correct application of expert procedures to assess security against these threats, as well as the subsequent mathematical-statistical and logical interpretation of the data obtained. The proposals for the use of methods of social diagnostics of information security in the practice of social management in the process of transformation of modern society on the basis of digital technologies have been explained.